Testate amoeba Rhogostoma minus Belar, 1921, associated with nodular gill disease of rainbow trout, Oncorhynchus mykiss (Walbaum) - Dyková, I; Tyml, T (Journal of fish diseases, 2016)
The case study targeted to determine the aetiology of nodular gill disease (NGD) of farmed rainbow trout. The methods included microscopical examination of gill material in fresh, culturing of isolated organisms, histology, transmission electron microscopy and molecular biology identification. The results revealed an intravital colonization of fish gills by the testate amoeba Rhogostoma minus Belar, 1921. Rhogostoma infection was found in all fish examined microscopically (15/15); in contrast, naked amoebae related to fully developed NGD lesions were found in minority of these fish (5/15). They belonged to four genera, Acanthamoeba, Vermamoeba, Naegleria and Vannella. Results presented in this study contribute to the mosaic of findings that contrary to amoebic gill disease of marine fish turn attention to the possibility of the heterogeneous, multi-amoeba-species and multifactorial aetiology of NGD.
Keywords: žábry; Fish Diseases; naked amoebae; zvířata; Oncorhynchus mykiss; Coinfection; Gills; nemoci ryb; Cercozoa; Rhogostoma minus; nodular gill disease; testate amoebae; koinfekce; Amebiasis; amébiáza; Animals